Influência da acurácia de completude na delimitação de áreas de preservação permanente - Mayara Soares de Sousa; Tony Vinicius Moreira Sampaio (Confins)
Since 1934 with the "Protective Forests" until 2012 with the "Permanent Preservation Areas", the Brazilian Forest Code foresees the creation of areas destined to the preservation of natural resources. Currently, Geographic Information Systems (GIS) associated with remote sensing products are presented as ancillary tools in the delimitation of PPA’s, because they have low cost and optimize the time necessary to identify and delimit them. This paper used techniques of Remote Sensing, photointerpretation and GIS to identify and quantify the existing springs in the watersheds of the Forquilha and Mirim Rivers, located in the Southwest of Paraná, in addition to delimited the Permanent Preservation Areas of springs and riverbanks of first order, using satellite imagery made available by Google in QGIS software version 2.16, using Open Layers Plugin tool. For this purpose, a classification key was constructed based on previous field knowledge, with some visible elements in the image that could indicate the presence of springs within the area of the watershed, the use of classification key made it possible to define areas of PPA in according to the Forestry Law Brazilian in force. The analysis resulted in the delimitation of 4.76 km² of PPA’s from springs and 18.31 km² of riverbanks, with an accuracy of 50.65% for the Forquilha River Basin, and 2.06 km² of springs, 7.69 km² of riverbanks, with an accuracy of 64.63% for the Mirim River Basin. These facts promoted an increase (commission) within the previously mentioned total, of Permanent Preservation Area of 2.13 km² (44.74%) and 7.44 (0.63%) of riverbanks for the Forquilha River Basin, and 0.70km² (33.98%) and 2.23 km² (29%) for the Mirim River Basin.